2007
DOI: 10.4049/jimmunol.178.4.2047
|View full text |Cite
|
Sign up to set email alerts
|

Differential CD40/CD40L Expression Results in Counteracting Antitumor Immune Responses

Abstract: Establishment of host-protective memory T cells against tumors is the objective of an antitumor immunoprophylactic strategy such as reinforcing T cell costimulation via CD40-CD40L interaction. Previous CD40-targeted strategies assumed that T cell costimulation is an all-or-none phenomenon. It was unknown whether different levels of CD40L expression induce quantitatively and qualitatively different effector T cell responses. Using mice expressing different levels of CD40L, we demonstrated that the greater the T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
37
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 38 publications
6
37
0
Order By: Relevance
“…In contrast, following 24 h infection with VV-WT or rVV40L, lower, nonsignificant increases of CD80 and PD-L1 levels were detected on treated monocytes. Figure 2B shows data from one representative experiment and summarizes the results obtained in three independent assays.Notably, CD1a induction, suggestive of a dendritic cell differentiation was undetectable in all culture conditions (data not shown).Taken together, these data underline the different biological properties of membrane-bound CD40L, as provided by a rVV40L controlled infection, as compared to its soluble form, possibly reflecting a differential cross-linking of CD40 receptor expressed on the surfaces of CD14 + monocytes [24,[26][27][28]. …”
supporting
confidence: 48%
“…In contrast, following 24 h infection with VV-WT or rVV40L, lower, nonsignificant increases of CD80 and PD-L1 levels were detected on treated monocytes. Figure 2B shows data from one representative experiment and summarizes the results obtained in three independent assays.Notably, CD1a induction, suggestive of a dendritic cell differentiation was undetectable in all culture conditions (data not shown).Taken together, these data underline the different biological properties of membrane-bound CD40L, as provided by a rVV40L controlled infection, as compared to its soluble form, possibly reflecting a differential cross-linking of CD40 receptor expressed on the surfaces of CD14 + monocytes [24,[26][27][28]. …”
supporting
confidence: 48%
“…We have shown that CD40 engagement by CD40L expressed by a tumor-cell vaccine can increase immunity against tumor antigens cross-presented by DCs [27] and that the CD40/CD40L axis is required for CTL induction by vaccination with GM-CSF/OX40L-transduced tumor cells [65]. T cells expressing high levels, but not low or null levels, of CD40L can adoptively transfer an efficient anti-tumor immunity [19]. We propose here that OX40 triggering can indirectly enhance CD40 stimulation to tumor-infiltrating DCs by increasing CD40L expression by tumor-infiltrating Tem cells, otherwise kept in a quiescent state.…”
Section: Discussionmentioning
confidence: 99%
“…The CD40/CD40L interaction is crucial for DC activation, survival and proliferation [26]. Many data suggest that this axis is involved in inducing protective anti-tumor immune response [18,19,27,28] and that activation of this pathway may represent a strategy for tumor treatment. To investigate whether OX86-induced tumor rejection was dependent on the CD40/CD40L axis, WT and CD40 À/À mice were inoculated subcutaneously with CT26 cells and treated intratumorally with OX86.…”
Section: Ox86-induced Tumor Rejection Requires the Cd40/cd40l Axismentioning
confidence: 99%
See 2 more Smart Citations